Oil Prices Fluctuations & Its Impact on Russians Economy; An Exchange Rate Exposure - Shafi, Khuram; Hua, Liu (Asian Journal of Economic Modelling, 2014)
Countries suffering from a shortage of oil reserves or importing oil are trying to reduce the oil consumption. But this can be only possible if alternatives of oil reserves are available. The factors affecting exchange rate are inflation, interest rate, foreign direct investment, government consumption expenditure and balance of trade. This paper seeks to identify the impact of oil prices and risk exposure of exchange rate volatility on economic growth in Russian economy on annual data of from year 1971 to 2012. Based on results it is estimated that imports, exports, inflation, interest rate, government consumption expenditure and foreign direct investment has a significant impact on real effective exchange rate in the long run and short run. Secondly, Engle Granger results indicate that relationship is significant in the long run and its error correction adjustment mechanism in short runs is significant and correctly signed for Russia.